Pengaruh Augmented Reality, Eco-Label, dan Green Trust Terhadap Keputusan Pembelian dengan Brand Equity Sebagai Variabel Iintervening: (Studi pada Konsumen Cat Avitex di Official Instagram @avianbrands) - Nyoga Fery Afriyanto; Amma Fazizah (Pusat Riset dan Inovasi Nasional, 2025)
Technology-based digital marketing and sustainability strategies are becoming essential in building brand competitiveness in the modern era. This study aims to examine and explain the influence of augmented reality, eco-label, and green trust on purchase decisions, with brand equity serving as a mediating variable. The population of this research consists of Avitex paint consumers who follow the official Instagram account @avianbrands and have made at least one purchase. A total of 150 respondents were selected using purposive sampling. The research employed an explanatory quantitative approach, and data were analyzed using path analysis with the assistance of SPSS version 22. The findings reveal that augmented reality, eco-label, and green trust have a significant effect on brand equity, which in turn significantly influences purchase decisions. Additionally, all three independent variables directly affect purchase decisions. The coefficient of determination (R²) value of 0.867 in model 1 and 0.759 in model 2 indicates a very strong relationship between variables. These results suggest that integrating digital innovation and environmental sustainability strategies can enhance brand equity and encourage environmentally conscious consumer purchasing behavior toward products like Avitex paint.